Can Internal Characteristics Prevent Fraud in Procurement of Goods and Services? - Wibowo, Krisna Mukti; Hardaningsih, Pancawati (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
Fraud in procurement of goods and services is not something new. There are many cases of fraud in procurement of goods and services, demanding us to review what factors can prevent fraud in procurement of goods and services. This research aimed to test whether organizational commitment, internal control, and integrity can prevent fraud in procurement of goods and services. This quantitative research used multiple regression analysis. The research samples, obtained using convenience sampling method, were 54 employees and village officials who had participated in procurement of goods and services. The research results show that organizational commitment and internal control do not influence prevention of fraud in procurement of goods and services, while integrity positively influences prevention of fraud in procurement of goods and services. The results of this research can be used to optimize the application of goods and services procurement system (e-procurement) by minimizing possible/potential constraints which may arise. Village government needs to optimize monitoring and evaluation routinely and continuously and assess any risks before decision making. It is also necessary to build the commitment of each of village officials as organizations responsible for village government’s better accountability capable of suppressing potential fraud.